Critical realism and information systems research: why bother with philosophy? - Philip J. Dobson (Information Research: An International Electronic Journal)
Garcia and Quek (1997) point out the difficulties in defining the actual object of information systems research - 'Is the object of research in information systems of a technological or social nature? Is it the organization, an information system or a social system?' (p. 450). A recent IFIP conference on Organisational and Social Perspectives on Information technology examines some of the social and organisational issues involved in IS Research (IFIP TC8 WG8.2, 2000). At this conference Jones (2000) examined the number of citations in the IFIP WG8.2 conference literature that refer to social theorists to determine the level of interest in the use of social theory in information systems research. Over the period 1979-1999 57% of papers had references to social theorists - the four major theorists being Giddens, Habermas, Foucault and Latour. This paper suggests that it would be useful to widen the range of social theorists used in IS to include that of Bhaskar who proposes a critical realist approach to social research. In order to highlight the main aspects of the philosophy the paper will critique a framework developed to suggest IS research approaches.